Rescue dawn [videorecording (DVD)] - Herzog, Werner, 1942-; Bale, Christian, 1974-; Zahn, Steve, 1968-; Davies, Jeremy, 1969-; Zeitlinger, Peter; Badelt, Klaus; Dunn, Annie (Metro-Goldwyn-Mayer Studios, 2007)
When U.S. fighter pilot Dieter Dengler escapes death after being shot down over one of the most intense front lines in the Vietnam War, his troubles were just beginning. He is taken captive by the Vietnamese Army and is forced to endure a harrowing stint in a Vietnamese prison camp. Dengler and a small band of his fellow captives stage a death-defying escape. Based on a true story.